Superiority indices as per ammi analysis to assess stability of faba bean (Vicia Faba L.) Genotypes - Arya, Rajesh Kumar; Dahiya, Gs; Verma, Ajay; Vandana, (Bangladesh Journal of Botany, 2023)
AMMI stability values along with adaptability measures MASV and MASV1 identified HB14-15, HB14-40, HB14-16 genotypes. Relative Performance of Genotypic Values (RPGV) measure had settled for HB14.32, HB14-18, HB14-14 genotypes. Superiority indexes allowed variable weights to yield and stability measures considered HB14.32, HB14-18, HB14-20 as of genotypes with high yield and stable performance. Highly significant variations due to environments (64.2%), GxE(11.4%) and genotypes (9.1%) were observed in AMMI analysis of Faba bean genotypes Hisar under field trials from rabi 2013-14 to rabi 2018-19. Biplot analysis had observed a cluster of RPGV, MHRPGV, along with the superiority measures as per arithmetic, geometric and harmonic means of yield values. Association analysis observed the stability measures W1, W2 and WAAS maintained direct relationship with AMMI based measures. Superiority indexes exhibited positive strong correlation with Sdev, PRVG and MHPRVG measures. Bangladesh J. Bot. 52(3): 723-730, 2023 (September)